Induction for senior house officers. Part I: The hospital programme - Ward, S. (BMJ Group, 1999)
The study was set up to examine how an induction programme can be designed to meet the needs and expectations of senior house officers (SHOs) beginning a new post in a hospital. A total of 63 SHOs, in five hospitals in the Anglia region, participated in standardised structured interviews up to 3 months after starting their post, by sorting a list of 38 possible induction topics in order of priority. Trainees' early induction needs were found to centre on day-one service activities, ie, information that enables them to undertake their service work efficiently and effectively, is particularly valued and required early. Information related to clinical education and training is also valued, but many trainees prefer it to be provided after they have been in post for a week or two. Much induction information can also be effectively conveyed in writing, with little or no need for additional formal presentation. We conclude that first-day induction programmes which strive to satisfy the range of trainee needs in one session fail to take account of the different priorities that trainees attach to induction information. Trainees do not want all information at once. Information of prime concern to clinical tutors, namely education, training and generic skills, is generally favoured after a week or two. To ensure that trainees' hospital induction needs are met in an efficient and effective way, programmes must be flexible and timely, and supported by comprehensive written information.   Keywords: induction; training; education